Pengembangan Komik Digital sebagai Media Edukasi Digital Native Hasil Transformasi Karakter Wayang Beber - Leny Suryani; Eko Hadi Prayitno; Agam Akbar Pahala (Besaung : Jurnal Seni Desain dan Budaya, 2026)
This study aims to develop a digital comic as an educational medium for digital natives through the transformation of Wayang Beber characters from the Wayang Museum collection. Using the ADDIE development model-Analysis, Design, Development, Implementation, and Evaluation, this research involved experts and digital-native users through interviews, questionnaires, documentation, and observation. The results show that digital natives have high interest in digital comics as a cultural learning medium. The evaluation results indicate that the comic achieved a 95.64% score in visual appearance, 90.77% in educational content, and 97.69% in media effectiveness, with an overall average of 94.7%, categorized as highly feasible and effective. The comic’s design successfully combines the traditional aesthetics of Wayang Beber with modern visual styles, making it engaging, easy to navigate, and educational. Overall, this study demonstrates that digital comics based on Wayang Beber transformation can serve as an innovative learning medium and a strategy for preserving Indonesian cultural heritage in the digital era.